Luminescence effect in amorphous PLT - Freitas, GFG; Nasar, R. S.; Cerqueira, M.; Melo, DMA; Longo, Elson [UNESP]; Pizani, P. S.; Varela, José Arana [UNESP] (Elsevier B.V., 2005)
Amorphous and crystalline powder of PLT phase was synthesized by using the Pechini method. Infrared (FTIR) analysis of the polymeric resin shows intense bands of organic materials from 250 to 1620 cm(-1). X-ray diffraction (XRD) and Raman spectra of calcined powder at different temperatures show amorphous phase at 450 degrees C/3 h, semi-crystalline phase at 550 degrees C/3 h and a crystalline phase at 800 degrees C/3 h. Luminescence effect was observed in amorphous powder calcined from 300 to 350 degrees/3 h with broad absorption peaks in 579 nm at 300 degrees C/3 h and 603 rum at 350 degrees C/3 h, respectively. The photoluminescence effect is attributed to emissions of Ti -> 0 directly from the oxygen 2p orbital (valence band) to the titanate 3d orbital (conduction bands). (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: amorphous materials; perovskites; PLT; (Pb, La)TiO3; luminescence